Efeitos da reposição hormonal com estrógeno em diferentes períodos após a ovariectomia na evolução da periodontite induzida em ratas - Spalding, Marianne [UNESP] (2005)
The aim of this study was to investigate the effect of different periods of estrogen replacement therapy onset on the progression of experimental periodontitis in ovariectomized rats. Sixty five female Wistar rats were ovariectomized and divided into two groups, experimental and control that received 17ß estradiol or vehicle, respectively. Each group was subdivided into five subgroups that started the treatment immediately, one, two, three and four weeks after the ovariectomy. Another eight rats underwent sham surgery. A month after ovariectomy or sham surgeries, a cotton ligature was placed around the maxillary second molars. Thirty five days after ligature placement, the animals were killed. It was analyzed the macroscopic, radiographic, microscopic and histometric aspects of the periodontal area. The results indicated that estrogen-deficient state may not have a direct effect on the alveolar bone adjacent to the maxillary second molar roots. Under the conditions of this experiment, estrogen replacement therapy did not delay the progression of induced periodontitis